1985
DOI: 10.1038/jcbfm.1985.24
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolic Rate Kinetic Model Parameter Determination in Humans: The Lumped Constants and Rate Constants for [18F]Fluorodeoxyglucose and [11C]Deoxyglucose

Abstract: The rate constants and lumped constants (LCs) for [18F]fluorodeoxyglucose ([18F]FDG) and [11C]deoxyglucose ([11C]DG) were determined in humans for the glucose metabolic rate kinetic model used to measure local cerebral glucose consumption. The mean values (+/- SE) of the LCs for [18F]FDG and [11C]DG are 0.52 +/- 0.028 (n = 9) and 0.56 +/- 0.043 (n = 6), respectively. The mean values (+/- SE) of the rate constants k*1, k*2, k*3, and k*4 for [18F]FDG for gray matter are 0.095 +/- 0.005, 0.125 +/- 0.002, 0.069 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
3
3

Year Published

1987
1987
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 393 publications
(191 citation statements)
references
References 36 publications
7
178
3
3
Order By: Relevance
“…5% glucose utilization in oxidative phosphorylation. [30][31][32][33][34] For rCMRglc analyses in this study, we applied a fixed lumped constant of 0.56, 23 which is a correction factor to convert FDG metabolic rate into rCMRglc determined from normal human brains. Since a previous study suggested that rCMRglc calculated with a fixed lumped constant would be underestimated at high metabolic rates and overestimated at low metabolic rates, 35 the rCMRglc in inflammatory (ROI PBR ) and infarct (ROI Infarct ) regions might be underestimated and overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…5% glucose utilization in oxidative phosphorylation. [30][31][32][33][34] For rCMRglc analyses in this study, we applied a fixed lumped constant of 0.56, 23 which is a correction factor to convert FDG metabolic rate into rCMRglc determined from normal human brains. Since a previous study suggested that rCMRglc calculated with a fixed lumped constant would be underestimated at high metabolic rates and overestimated at low metabolic rates, 35 the rCMRglc in inflammatory (ROI PBR ) and infarct (ROI Infarct ) regions might be underestimated and overestimated.…”
Section: Discussionmentioning
confidence: 99%
“…For quantification of grey matter glucose metabolism, a set of rate constants K1-k4 and a lumped constant were used (Phelps et al, 1979;Reivich et al, 1985). Cortical Regions-of-Interest were manually drawn to calculate the mean cortical rMRGlu for each condition (influx, elimination, placebo).…”
Section: Absolute Quantification Of Cerebral Glucose Metabolismmentioning
confidence: 99%
“…Two glucose analogs have been labeled with positron emitters and have been successfully used: carbon-II-labeled 2-deoxy-o-glucose (2DG) and 2-esF]fluoro-2-o-deoxyglucose (FDG) (Phelps et aI., 1979b;Reivich et aI., 1979Reivich et aI., , 1982. In normal subjects, these methods have been partially vali dated since they provide CMRglc values that are in agreement with whole brain CMRglc values pro vided by the Kety-Schmidt method, and the "lumped constant" has now been independently measured by Reivich et al (1985) both for 2DG and FDG (although the inherent assumption that k4 = 0 was made). This method has been subjected to an extensive analysis of model-related errors and lim itations and numerous refinements have been pub lished since its first description (Huang et aI., 1980(Huang et aI., , 1981Brooks, 1982;Wienhard et aI., 1985;Hutchins et aI.…”
Section: Deoxyglucosementioning
confidence: 99%